Effect of Dietary Fatty Acids on Sleep and Stress Among Adults With Migraine: Secondary Analysis of a Randomized Controlled Trial. (14th June 2022) - Faurot, Keturah; Horowitz, Mark; Ramsden, Christopher; Mann, John; Zamora, Daisy
Abstract: Objectives: To determine whether dietary interventions that reduce headache also improve sleep and stress in adults with migraine. Methods: We conducted a 16-week, three arm, parallel group, randomized, modified double blind, controlled trial in North Carolina. Participants were 182 adults (88% women, mean age 38y) with migraines on 5–20 days per month. The 3 diets were designed with EPA, DHA, and linoleic acid altered as controlled variables: H3 diet (n = 61)—increase EPA + DHA to 1.5 g/day and maintain linoleic acid at around 7% of energy; H3L6 diet (n = 61)—increase n-3 EPA + DHA to 1.5 g/day and decrease linoleic acid to ≤ 1.8% of energy; control diet (n = 60)—maintain EPA + DHA at <150 mg/day and linoleic acid at around 7% of energy. Sleep quality, stress rating, and the number of headache hours per day were pre-specified endpoints assessed daily with an electronic diary. Sleep quality was rated on a 1–4 scale, with higher score indicating better quality. Stress was rated on a 0–10 scale, with higher score indicating more stress. Longitudinal mixed models were used to estimate between-group differences at end of study. Mediation analyses examining headache hours as a mediator ( paramed command in Stata 17) controlled for baseline BMI, age, sex, headache hours, and baseline values of the respective outcome. Results: At baseline, mean sleep quality was 2.5 (SD 0.5) and stress rating was 3.0 (SD 1.6). In intention-to-treat analyses, the H3L6 group significantly increased sleep quality and reduced stress level relative to the control group (difference 0.2, 95% confidence interval 0.05 to 0.3; −0.6, −0.9 to −0.3, respectively). There was a similar trend in the H3 vs. control group, although only statistically significant for increased sleep quality (0.1, 0.02 to 0.2) but not for reduced stress rating (−0.3, −0.6 to 0.02). In mediation analyses, the reduction in headache hours per day explained ∼60% of the effect of the combined interventions on sleep quality (natural indirect effect = 0.09, p = 0.006). For stress, the reduction in headache hours per day explained ∼45% of the effect of the combined interventions (natural indirect effect = −0.14, p = 0.078). Conclusions: The H3L6 intervention improved sleep quality and decreased stress. Findings suggest that these improvements occurred partially as a result of headache reduction. Funding Sources: NCCIH.